DETERMINANTS OF EMPLOYEE PERFORMANCE : EVIDENCE FROM A LOCAL GOVERNMENT INSTITUTION - Basilius Agung Tirta Buana; Didik Subiyanto; Eko Yulianto (Widya Dharma Journal of Business - WIJoB, 2026)
This study aims to determine the influence of work motivation, work environment, and work engagement on employee performance at the Lempuing Subdistrict Office in Ogan Komering Ilir Regency. This study employs a quantitative approach using a questionnaire-based data collection method. The sampling technique utilizes non-probability sampling via the saturation sampling method, thereby including all employees at the Lempuing Subdistrict Office in Ogan Komering Ilir Regency as the study sample. The collected data were analyzed using IBM SPSS Statistics version 25 to test the relationships and influences among the study variables. The results indicate that both work motivation and work engagement have positive and significant effects on employee performance, while the work environment does not have a significant effect on employee performance. Furthermore, work motivation, work environment, and work engagement simultaneously have a significant effect on employee performance at the Lempuing Subdistrict Office, Ogan Komering Ilir Regency. This study is expected to serve as a basis for the Lempuing Subdistrict Office in Ogan Komering Ilir Regency in formulating policies and strategies to improve employee performance, as well as to optimize the factors that influence employee performance.